NIV Zondervan study Bible built on the truth of scripture and centered on the gospel message - Carson, D. A. 1946- (Grand Rapids, Mich. Zondervan, 2015)
The NIV Zondervan Study Bible, featuring Dr. D.A. Carson as general editor, is built on the truth of Scripture and centered on the gospel message. An ambitious and comprehensive undertaking, Dr. Carson, with committee members Dr. T. Desmond Alexander, Dr. Richard S. Hess, Dr. Douglas J. Moo, and Dr. Andrew David Naselli, along with a team of over 60 contributors from a wide range of evangelical denominations and perspectives, crafted all-new study notes and other study tools to present a biblical theology of God's special revelation in the Scriptures. To further aid the readers' understanding of the Bible, also included are full-colour maps, charts, photos and diagrams. In addition, a single-column setting of the Bible text provides maximum readability. The accessible and fresh interior design will capture your attention and enhance your study experience
"New international version"
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible <English>; Bible -- Study and teaching -- Bible; Study skills -- Study guides -- Study guides; Einführung